2006
DOI: 10.1097/01.mpa.0000220857.55378.7b
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Body Overweight and Class I, II and III Obesity on the Outcome of Acute Biliary Pancreatitis

Abstract: In acute biliary pancreatitis, body overweight and obesity represent a risk of more "severe" disease and the number and type of complications increase in categories of increasing BMI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
58
0
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(65 citation statements)
references
References 19 publications
(7 reference statements)
5
58
0
2
Order By: Relevance
“…In a meta-analysis, obesity (defined as BMI >30) was associated with significantly higher incidence of systemic and local complication and higher rate of mortality [1][2][3]. Several independent studies have also confirmed this observation [4][5][6].…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…In a meta-analysis, obesity (defined as BMI >30) was associated with significantly higher incidence of systemic and local complication and higher rate of mortality [1][2][3]. Several independent studies have also confirmed this observation [4][5][6].…”
Section: Discussionsupporting
confidence: 55%
“…Results from meta-analysis show that obesity (defined as BMI>30) was associated with significantly higher incidence of systemic and local complication and higher rate of mortality from AP [1][2][3]. Several independent studies have also confirmed this observation [4][5][6]. Visceral obesity, which is a component of metabolic syndrome, has been recognized to have a stronger correlation with poor outcomes in patients with AP [1][2][3][4][5][6][7].…”
Section: Introductionsupporting
confidence: 48%
See 1 more Smart Citation
“…In 35 reports the exact Atlanta definitions for organ failure were specifically stated and used 23,61,62 . Seven articles restricted organ failure to two of the four Atlanta determinants for organ failure: respiratory and renal insufficiency 63 -65 .…”
Section: Organ Failurementioning
confidence: 99%
“…In severe cases, progress to circulatory shock, acute lung injury, renal failure, and eventual death may occur (1). Despite some controversy, numerous studies have demonstrated that obesity is associated with increased risk of the severe form of AP and with development of life-threatening complications (2)(3)(4)(5)(6)(7)(8). However, the mechanism by which increased adiposity worsens AP remains unknown.…”
mentioning
confidence: 99%